Pengaruh Quick Response Code Indonesian Standard (QRIS) terhadap Minat Beli Masyarakat (Studi Kasus di Distrik Manokwari Barat) - Sasea, Revival; Rumere, Victor Sasea; Bauw, Siti Aisah (Fakultas Ekonomi dan Bisnis, Universitas Papua, 2025)
The success of a payment system is largely determined by the advantages offered by its features, such as the Quick Response Indonesian Standard (QRIS). This research aims to explore the inherent features of QRIS—specifically convenience, speed, and security—and how they influence people's purchasing interest in the Manokwari District of Manokwari Regency. We utilized primary data collected from informant responses through questionnaires distributed via Google Forms. The data were analyzed using a multiple linear regression approach with Ordinary Least Squares. The findings indicate that both convenience and speed significantly and positively impact people's purchasing interest in West Manokwari District. In contrast, the security factor does not have a significant effect on shopping interest. Consequently, the policy implications suggest enhancing citizens' knowledge of digital financial literacy and strengthening digital financial infrastructure to improve the convenience of using QRIS for shopping transactions. The success of a payment system is largely determined by the advantages offered by its features, such as the Quick Response Indonesian Standard (QRIS). This research aims to explore the inherent features of QRIS—specifically convenience, speed, and security—and how they influence people's purchasing interest in the Manokwari District of Manokwari Regency. We utilized primary data collected from informant responses through questionnaires distributed via Google Forms. The data were analyzed using a multiple linear regression approach with Ordinary Least Squares. The findings indicate that both convenience and speed significantly and positively impact people's purchasing interest in West Manokwari District. In contrast, the security factor does not have a significant effect on shopping interest. Consequently, the policy implications suggest enhancing citizens' knowledge of digital financial literacy and strengthening digital financial infrastructure to improve the convenience of using QRIS for shopping transactions.